Silicon carbon material, preparation method thereof and lithium ion battery
By using silicon carbon materials with an alternating layer structure of central core and silicon carbon in lithium-ion batteries, the problem of insufficient resistance to voltage, cycle and rate in high-energy density batteries is solved, and higher compressive strength and battery performance are achieved.
Patent Information
- Application Number
- CN202411853666.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-25
AI Technical Summary
Existing silicon carbon materials show insufficient voltage resistance, cycle performance and rate performance in high-energy density lithium-ion batteries, which cannot meet the needs of modern battery development.
A silicon-carbon material is made of a central core and a silicon-carbon alternating layer structure coated on its surface. The silicon-carbon alternating layer consists of alternately arranged silicon layers and carbon layers. The carbon layer is a soft-carbon-like structure and is prepared by chemical vapor deposition.
The compressive strength of silicon-carbon materials and the performance of the battery in terms of circulation and magnification are improved, ensuring the high energy density and stability of the battery.
Smart Images

Figure CN119695109A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a silicon-carbon material and a preparation method thereof, and a lithium-ion battery. Background Art
[0002] Silicon-carbon negative electrode materials have become a powerful lever for the development of high-energy-density energy batteries because of their extremely high gram capacity. Its lithium insertion potential is about 0.4V, so it can maintain a low operating voltage while maintaining extremely high rate performance. The new silicon-carbon negative electrode material is obtained by deposition on a porous carbon surface with a high specific surface area, and its main improvement comes from the improvement of the core-shell structure and the yolk-shell structure. However, for the current high-energy-density system, its voltage resistance performance has been difficult to meet the requirements. Furthermore, when it is applied to batteries, its cycle performance and rate performance cannot meet the needs of today's development. Summary of the invention
[0003] In order to overcome the defects of poor strength of silicon-carbon materials in the prior art, poor cycle performance and rate performance when used in batteries, a silicon-carbon material and a preparation method thereof, and a lithium-ion battery are provided. The silicon-carbon material has high strength and has excellent cycle performance and rate performance when used in batteries.
[0004] The present invention solves the above problems through the following solutions:
[0005] The present invention provides a silicon-carbon material, which comprises a central core and a surface silicon-carbon alternating layer coated on the central core, wherein the silicon-carbon alternating layer comprises at least one silicon layer and at least one carbon layer, wherein the silicon layer and the carbon layer are alternately arranged, wherein the layer adjacent to the central core is a silicon layer, and the outermost layer of the concentric circle structure is a carbon layer;
[0006] The central core is a carbon sphere, the ID / IG value of the central core is 0.2-0.7, and the specific surface area of the central core is 60-300m 2 / g;
[0007] Wherein, the carbon layer is a soft carbon-like structure.
[0008] In the present invention, the concentric circle structure is not a concentric circle structure in a geometric sense, but a spherical structure with a ball as the core and layers of coatings; the soft carbon-like structure refers to soft carbon or a material mainly composed of soft carbon.
[0009] In the present invention, preferably, the silicon-carbon material is a concentric circle structure.
[0010] In the present invention, preferably, in the silicon-carbon alternating layer, the thickness ratio of every two adjacent carbon layers to silicon layers is (0.2-10):1.
[0011] In certain specific embodiments of the present invention, in the silicon-carbon alternating layers, the thickness ratio of every two adjacent carbon layers to silicon layers is 51:49, 45:55, 38:62, 35:65, 30:70, 23:77, 20:80 or 18:83.
[0012] In the present invention, preferably, the number of the silicon layers is 3-20 layers, for example, 10 layers.
[0013] In the present invention, preferably, the silicon-carbon material I 0.45 The value is less than 55mah / v.
[0014] In certain specific embodiments of the present invention, the silicon-carbon material I 0.45 The values are 18.7mah / v, 22.6mah / v, 24.5mah / v, 29.8mah / v, 35.4mah / v, 43.6mah / v, 47.9mah / v or 54.3mah / v.
[0015] In the present invention, preferably, the silicon-carbon material I 0.45 Value / I 0.30 The value is less than 4.
[0016] In the present invention, the silicon-carbon material I 0.45 The value is the dQ / dV value corresponding to the voltage of 0.45V in the voltage-dQ / dV curve of silicon carbon material; the I 0.30 The value is the dQ / dV value corresponding to the voltage of 0.30V in the voltage-dQ / dV curve of silicon carbon material. 0.45 The value can be used to reflect the amorphous properties of silicon-carbon materials. The smaller the value, the better the amorphous properties.
[0017] In the present invention, preferably, the size of the silicon crystal with 2θ of 28° is 1-2 μm.
[0018] In the present invention, preferably, the true density of the central core is 1.5-2.5 g / cm 3 , for example 2.2 g / cm 3 or 1.98 g / cm 3 .
[0019] In the present invention, preferably, the silicon content of the silicon-carbon material is 50%-85%, for example, 51.3%, 57.9%, 63.1%, 68.6%, 73.6%, 78.9%, 81.1% or 84.5%. The silicon content means the mass percentage of silicon in the silicon-carbon material.
[0020] In the present invention, preferably, the carbon content of the silicon-carbon material is 15%-50%, for example, 48.7%, 42.1%, 36.9%, 31.4%, 26.4%, 21.1%, 18.9% or 15.5%. The carbon content means the mass percentage of carbon in the silicon-carbon material.
[0021] In the present invention, preferably, the ID / IG value of the central core is 0.3-0.6, for example, 0.4.
[0022] In the present invention, preferably, the specific surface area of the central core is 10-200m 2 / g, for example, 121m 2 / g or 50m 2 / g.
[0023] In the present invention, preferably, the D50 particle size of the central core is 0.5-3 μm, for example, 1 μm.
[0024] In the present invention, preferably, the (D90-D10) / D50 value of the central core is 0.5-5, for example, 1.
[0025] In certain preferred embodiments of the present invention, the specific surface area of the central core is 60-300m 2 / g.
[0026] In certain specific embodiments of the present invention, the specific surface area of the silicon-carbon material is 1-5 m 2 / g, for example, 3.9m 2 / g, 4m 2 / g, 4.1m 2 / g, 4.2m 2 / g or 4.3m 2 / g.
[0027] The present invention also provides a method for preparing a silicon-carbon material, which comprises the following steps:
[0028] Performing silicon-carbon alternating deposition on the central nucleation point; the silicon-carbon alternating deposition includes at least one silicon deposition and at least one carbon deposition, the silicon deposition and the carbon deposition are performed alternately, and the first deposition is silicon deposition, and the last deposition is carbon deposition;
[0029] The central nucleation point is a carbon sphere, the ID / IG value of the central nucleation point is 0.2-0.7, and the specific surface area of the central nucleation point is 60-300m 2 / g;
[0030] Wherein, the carbon deposition adopts a carbon source with a molecular weight of 100-1000.
[0031] In the present invention, the ID / IG value is used to characterize the degree of graphitization. The lower the ID / IG value, the higher the degree of graphitization.
[0032] In the present invention, preferably, the ID / IG value of the central nucleation point is 0.3-0.6, for example, 0.4.
[0033] In the present invention, preferably, the specific surface area of the central nucleation point is 60-200m 2 / g, for example, 121m 2 / g.
[0034] In the present invention, preferably, the true density of the central nucleation point is 1.5-2.5 g / cm 3 , for example 2.2 g / cm 3 or 1.98 g / cm 3 .
[0035] In the present invention, preferably, the D50 particle size of the central nucleation point is 0.5-3 μm, for example, 1 μm.
[0036] In the present invention, preferably, the (D90-D10) / D50 value of the central nucleation point is 0.5-5, for example, 1.
[0037] In certain specific embodiments of the present invention, the central nucleation point is acetylene black or mesophase microspheres.
[0038] In the present invention, preferably, the number of times of silicon deposition is 3-20 times, for example, 10 times.
[0039] In the present invention, the carbon source is a high molecular weight carbon source. Compared with a low molecular weight carbon source, a high molecular weight carbon source is more inclined to form a soft carbon-like structure.
[0040] In the present invention, the molecular weight of the carbon source is 100-1000, preferably 150-1000, such as 178, 200, 500 or 1000.
[0041] In the present invention, the carbon source may be one or more of condensed ring aromatic hydrocarbons, a mixture containing condensed ring aromatic hydrocarbons, an alkane, a mixture containing an alkane, and asphalt.
[0042] Wherein, the number of C atoms of the alkane is preferably 10-30.
[0043] In some preferred embodiments of the present invention, the carbon source is one or more of anthracene, anthracene oil, coal tar pitch and paraffin, wherein anthracene oil is a mixture containing anthracene.
[0044] In certain specific embodiments of the present invention, the carbon source is anthracene oil, and the molecular weight of the anthracene oil is preferably 1,000.
[0045] In certain specific embodiments of the present invention, the carbon source is anthracene.
[0046] In the present invention, preferably, the silicon deposition is performed by chemical vapor deposition.
[0047] Preferably, the temperature of silicon deposition is 450-700°C, more preferably 500-700°C, for example 550°C.
[0048] In certain specific embodiments of the present invention, the silicon deposition temperature is 450-600°C.
[0049] Preferably, before silicon deposition is performed, the temperature of the environment in which the silicon source used for the silicon deposition is located is maintained at 300-400°C, for example, 350°C.
[0050] Preferably, the flow rate of the silicon source gas is 0.5-50 L·kg -1 ·min -1 , for example 5L·kg -1 ·min -1 .
[0051] Preferably, the silicon deposition time is 1-40 min, more preferably 1-30 min.
[0052] In certain specific embodiments of the present invention, the silicon deposition time is 5 min, 10 min, 15 min, 20 min, 25 min, 30 min, 35 min or 40 min.
[0053] In the present invention, preferably, the carbon deposition is performed by chemical vapor deposition.
[0054] Preferably, the temperature of the carbon deposition is 600-1000°C, for example, 800°C.
[0055] Preferably, the carbon deposition time is 1-100 min, for example, 5 min.
[0056] Preferably, before the carbon deposition is performed, the temperature of the environment in which the carbon source used for the carbon deposition is located is maintained at 300-400°C, for example, 350°C.
[0057] Preferably, the flow rate of the carbon source gas is 0.5-50 L·kg -1 ·min -1 , for example 5L·kg -1 ·min -1 .
[0058] The carbon deposition preferably also uses a protective gas, such as one or more of nitrogen, helium and argon.
[0059] Wherein, the protective gas and the carbon source gas are introduced in the form of mixed gas.
[0060] Wherein, the flow rate of the mixed gas is 1-100L·kg -1 ·min -1 , for example, 10L kg -1 ·min -1 .
[0061] The flow rate of the protective gas is 0.5-50 L·kg -1 ·min -1 , for example 5L·kg -1 ·min -1 .
[0062] Before the carbon deposition is performed, the temperature of the environment in which the carbon source and the protective gas used for the carbon deposition are located is preferably maintained at 300-400°C, for example, 350°C.
[0063] Before forming the carbon source gas, the temperature of the environment where the carbon source is located is preferably maintained at 300-400°C, for example, 350°C.
[0064] Before forming the carbon source gas, the pressure of the environment where the carbon source is located is preferably maintained at 20Kpa-80Kpa.
[0065] In certain specific embodiments of the present invention, before forming the gas of the carbon source, the pressure of the environment of the carbon source is maintained at 50 kPa.
[0066] In the present invention, preferably, the preparation method of the silicon-carbon material is carried out in a vapor deposition device, which includes a gas generator, a mixer and a reaction furnace; the gas generator is provided with a first gas outlet, the mixer includes a first gas inlet, a second gas inlet and a deposition gas outlet arranged at different positions, the reaction furnace is provided with a deposition gas inlet, the first gas outlet of the gas generator is connected to the first gas inlet of the mixer, and the deposition gas outlet of the mixer is connected to the deposition gas inlet of the reaction furnace;
[0067] When carbon deposition is performed, the gas generator is used to generate a carbon source gas, the carbon source gas is sequentially introduced into the mixer through the first gas outlet and the first gas inlet of the mixer, and then sequentially enters the reaction furnace through the deposition gas outlet of the mixer and the deposition gas inlet of the reaction furnace; carbon deposition is performed in the reaction furnace;
[0068] When silicon deposition is performed, the silicon source gas used for the silicon deposition is introduced into the mixer through the second gas inlet, and then enters the reaction furnace through the deposition gas outlet of the mixer and the deposition gas inlet of the reaction furnace in sequence, and silicon deposition is performed in the reaction furnace.
[0069] The present invention also provides a silicon-carbon material obtained by the method for preparing the silicon-carbon material.
[0070] The present invention also provides a lithium ion battery, which comprises the silicon-carbon material as described above.
[0071] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.
[0072] The reagents and raw materials used in the present invention are commercially available.
[0073] The positive and progressive effects of the present invention are:
[0074] The present invention adopts a specific central nucleation point and a specific carbon source to cooperate with each other, and the prepared silicon-carbon material includes a central core and a silicon-carbon alternating layer from the inside to the outside. The central core with a specific graphitization degree and specific surface area and the carbon layer with a specific structure cooperate with each other, so that the silicon-carbon material has an extremely high compressive strength and also has an excellent effect of relieving expansion, and can reduce the disadvantages of poor rate and the like; the silicon-carbon material of the present invention has a high carbon content and good silicon amorphousness. The preparation method of the present invention is simple in steps and has a low production cost.
[0075] The silicon-carbon material of the present invention can have excellent cycle performance and rate performance when applied to batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0076] Figure 1 This is a schematic diagram of the structure of the device used for the alternating deposition of silicon and carbon in Example 1.
[0077] Figure 2 This is a schematic plan view of the structure of the silicon-carbon material prepared in Example 1.
[0078] Figure 3 This is a schematic plan view of the structure of the silicon-carbon material prepared in Example 2-4.
[0079] Figure 4 This is a three-dimensional schematic diagram of the structure of the silicon-carbon material prepared in Example 1-8.
[0080] Figure 5 This is the TEM-EDS image of the silicon-carbon material prepared in Example 1.
[0081] Figure 6This is a voltage-dQ / dV curve of the silicon-carbon material prepared in Example 4.
[0082] The reference numerals are as follows:
[0083] 1-gas generator; 2-mixer; 3-reaction furnace;
[0084] 101 - first gas inlet; 102 - second gas inlet; 103 - deposition gas outlet. DETAILED DESCRIPTION
[0085] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.
[0086] The mesophase microspheres used in the following examples and comparative examples were purchased from Shanghai Shanshan Technology Co., Ltd., model G15; the phenolic resin carbonized balls were purchased from Shengquan, model JF-200H.
[0087] Example 1
[0088] The preparation of silicon carbon material includes the following steps:
[0089] The central nucleation point is a solid structure of the mesophase microspheres, and its related parameters are listed in Table 1.
[0090] The central nucleation point is subjected to 10 times of alternating silicon-carbon deposition, specifically, silicon deposition, carbon deposition, silicon deposition, carbon deposition, ... are sequentially performed until the cycle is completed after 10 times, thereby obtaining a silicon-carbon material.
[0091] Silicon-carbon alternating deposition is carried out in a vapor deposition device: the structure of the vapor deposition device is as follows Figure 1 As shown, the vapor deposition device includes a gas generator 1, a mixer 2 and a reaction furnace 3; the gas generator 1 is provided with a first gas outlet, the mixer 2 includes a first gas inlet 101, a second gas inlet 102 and a deposition gas outlet 103 arranged at different positions, the reaction furnace 3 is provided with a deposition gas inlet, the first gas outlet of the gas generator 1 is connected to the first gas inlet 101 of the mixer 2, and the deposition gas outlet 103 of the mixer 2 is connected to the deposition gas inlet of the reaction furnace 3.
[0092] The specific process of silicon-carbon alternating deposition is:
[0093] During the first silicon deposition, the silicon source monosilane gas was introduced into the mixer at 350°C through the first gas inlet at a flow rate of 5 L kg -1 ·min -1; The silicon source is introduced into the heater from the mixer through the deposition gas outlet and contacts the central nucleation point placed in the heater for silicon deposition; the time for a single introduction of the silicon source is 5 minutes, that is, the time for silicon deposition is 5 minutes, and the temperature of silicon deposition is 550°C.
[0094] During the first carbon deposition, nitrogen was introduced into the mixer at 350°C through the first gas inlet at a flow rate of 5 L kg -1 ·min -1 The carbon source anthracene oil (purchased from Shandong Lingchuang Chemical) was placed in a gas generator at a temperature of 350°C and an absolute pressure of 50 kPa, so that the anthracene oil formed anthracene oil gas and heated to 5 L·kg -1 ·min -1 The flow rate is passed through the second gas inlet into the mixer at 350°C; the nitrogen and anthracene oil gases are evenly mixed in the mixer and then passed into the heater through the deposition gas outlet, and contact with the central nucleation point placed in the heater after the first silicon deposition for carbon deposition; the time for a single carbon source introduction is 5 minutes, that is, the carbon deposition time is 5 minutes, and the temperature of silicon deposition is 800°C.
[0095] The second silicon deposition is performed after the first carbon deposition. The second silicon deposition is a repetition of the first silicon deposition operation. The second carbon deposition is a repetition of the first carbon deposition operation. The silicon and carbon depositions are performed alternately in this way.
[0096] The silicon-carbon material prepared in Example 1 is a concentric circle structure, which includes a central core and a surface silicon-carbon alternating layer coated on the central core, the silicon-carbon alternating layer includes 10 silicon layers and 10 carbon layers, the silicon layers and the carbon layers are alternately arranged, the layer adjacent to the central core is a silicon layer, and the outermost layer of the concentric circle structure is a carbon layer; wherein the central core is a carbon sphere, and the ID / IG value of the central core is the same as the ID / IG value, specific surface area and true density of the central nucleation point; wherein the carbon layer is a soft carbon-like structure. The specific structure of the silicon-carbon material prepared in Example 1 is as follows Figure 2 As shown, the number of silicon layers and carbon layers is only for illustration, and there are actually 10 silicon layers and 10 carbon layers.
[0097] The preparation of the pole piece includes the following steps:
[0098] The formula of the negative electrode sheet is CMC: PAA: SBR: SP: CNTs: the above silicon-carbon materials: graphite = 0.5: 2.5: 1: 1: 0.1: X: 95.9-X, wherein X is automatically matched with the mass of silicon accounting for 5% of the solid content of the negative electrode slurry, and the solid content of the negative electrode slurry is the mass ratio of the solid in the negative electrode slurry to the mass of the negative electrode slurry.
[0099] The steps for preparing the negative electrode slurry are as follows: add graphite, CMC, silicon-carbon material, SP and CNTs in sequence, then disperse for 3 hours with a planetary disperser at a rotation speed of 300r / min and a revolution of 1000r / min, inject 80% of the mass of deionized water required to make the solid content of the negative electrode slurry 40% at one time, rotate at 500r / min and rotate at 600r / min for 1 hour, then add PAA and disperse at a rotation speed of 500r / min and a revolution of 500r / min for 1 hour, inject the remaining 20% of deionized water, and finally add SBR and disperse at a rotation speed of 300r / min and a revolution of 300r / min for 1 hour to obtain the negative electrode slurry.
[0100] Preparation of negative electrode sheet: The coated current collector uses 8μm thick copper foil, double-sided coating, the coated side faces the negative electrode of the button battery, and the thickness of the negative electrode slurry coated on one side is about 40μm, with a compaction density of 1.8g / cm 3 The coating speed is 40 cm / s, the baking temperature is 80°C, the drying time is 400s, and the negative electrode sheet is obtained after drying.
[0101] Embodiment 2-9
[0102] In the preparation of the silicon-carbon materials of Examples 2-9, except for the time of introducing the silicon source once, the other conditions are the same as those of Example 1.
[0103] The silicon-carbon material prepared in Example 2-9 is a concentric circle structure, which includes a central core and a surface silicon-carbon alternating layer coated on the central core, the silicon-carbon alternating layer includes 10 silicon layers and 10 carbon layers, the silicon layers and the carbon layers are alternately arranged, the layer adjacent to the central core is a silicon layer, and the outermost layer of the concentric circle structure is a carbon layer; wherein the central core is a carbon sphere, and the ID / IG value of the central core is the same as the ID / IG value, specific surface area and true density of the central nucleation point; wherein the carbon layer is a soft carbon-like structure. The specific structure of the silicon-carbon material prepared in Example 2-4 is as follows Figure 3 As shown, the number of silicon layers and carbon layers is only for illustration, and there are actually 10 silicon layers and 10 carbon layers. The three-dimensional schematic diagram of the structure of the silicon-carbon material prepared in Example 1-8 is shown in Figure 4 shown.
[0104] The preparation of the pole pieces of Examples 2-9 is the same as that of Example 1.
[0105] Among them, the carbon source in Example 9 is anthracene, and its molecular weight is 178.
[0106] Comparative Example 1
[0107] The preparation method of the silicon-carbon material of Comparative Example 1 comprises the following steps:
[0108] S1. Preparation of precursor: 1 kg of phenolic resin (phenolic resin purchased from Hubei Hengye Technology Co., Ltd., model 2135), 2 kg of alcohol, and 60 g of hexamethylenetetramine (HMT) were mixed and dispersed with a high-speed homogenizer at a speed of 2000 r / min for 60 min. At 130°C, the mixture was spray-dried to a particle diameter of 8 μm;
[0109] S2. Preparation of carbon materials: The spray-dried powder was placed in a rotary furnace for cross-linking at 10 r / min and then carbonized. The heating curve for the first stage was 4°C / min for 50 min and then heated to 200°C for 1 h. The main purpose was to cross-link the phenolic resin. The heating curve for the second stage was 4°C / min for 113 min. The nitrogen atmosphere protection gas supply rate was 1 L·kg -1 ·min -1 ;
[0110] S3. Activation of carbon materials: Porous carbon was obtained by activation in CO2 atmosphere for 9 h with a gas supply rate of 2 L·kg -1 min -1 The furnace temperature is 550℃, and the specific surface area of the porous carbon is 1890m 2 / g, micropores account for 85.3%, mesopores account for 14.7%, and the pore volume is 1.32cm 3 / g;
[0111] S4, silicon deposition: the atmosphere was switched to a silane mixture (20% silane and 80% argon by mass), and the core was deposited at 500°C for 10 h with a ventilation volume of 15 L kg -1 ·min -1 Then switch the atmosphere to an acetylene mixture (20% acetylene and 80% argon by mass), with a ventilation volume of 5 L kg -1 ·min -1 , continue to deposit at 500°C for 10h, then switch to nitrogen, and then cool to room temperature 25°C to obtain a porous carbon-supported silicon substrate precursor;
[0112] S5. Acetylene coating: The atmosphere is switched to acetylene for coating, where the acetylene ventilation volume is 2L·kg -1 ·min -1 , time is 10 hours, temperature is 550°C, and the silicon-carbon material of Comparative Example 1 is obtained.
[0113] Comparative Examples 2-7
[0114] In the preparation of the silicon-carbon materials of Comparative Examples 2-7, except that the data listed in Table 1 are different from those in Example 1, the other conditions are the same as those in Example 1.
[0115] Among them, the carbon source of Comparative Example 2 is petroleum asphalt, and its number average molecular weight is 22000; the carbon source of Comparative Example 9 is propane, and its molecular weight is 44; the carbon source of Comparative Example 7 is paraffin, and its number average molecular weight is 2000.
[0116] The preparation of the pole pieces of Comparative Examples 2-7 is the same as that of Example 1.
[0117] Table 1
[0118]
[0119]
[0120] Effect Example 1
[0121] The silicon-carbon materials prepared in the above Examples 1-9 and Comparative Examples 1-7 were subjected to the following tests:
[0122] 1. Determination of carbon content and silicon content of silicon-carbon materials: Use a high-frequency carbon-sulfur analyzer (model DK-606) to measure the carbon content and sulfur content respectively, silicon content = 1-carbon content-sulfur content. Nicolet 6700 Fourier transform infrared spectrometer can assist in testing the carbon content of silicon-carbon materials.
[0123] 2. Determination of specific surface area of silicon-carbon materials: NT8000 is used to test the specific surface area.
[0124] 3. Particle size test: A laser particle size analyzer was used to test the D50 particle size of silicon-carbon materials at pressures of 0T, 5T, 10T, 15T and 20T respectively.
[0125] 4. The thickness ratio of every two adjacent carbon layers and silicon layers in the silicon-carbon alternating layer:
[0126] Take 10g of silicon-carbon material, test it with a true density tester at 0.1MPa to obtain the apparent volume V1 of the silicon-carbon material, and test it at 1MPa to obtain the real volume V2 and void volume (V1-V2) of the silicon-carbon material; soak it in hydrofluoric acid for 10h, add NMP and then wash it with deionizer to obtain a carbon skeleton, test it at 1MPa to obtain the real volume V3 of the carbon skeleton, and the volume of the silicon material is V2-V3. It can be obtained that the total volume ratio of the carbon skeleton to the silicon material is =V3 / (V2-V3), which is approximately the average ratio of the thickness ratio of each two adjacent carbon layers to silicon layers, recorded as the thickness ratio of each two adjacent carbon layers to silicon layers.
[0127] 5.I 0.45 Value test: I of silicon carbon material 0.45 The test instrument is Xinwei CE-6000 to obtain the voltage-dQ / dV curve of silicon carbon material. The dQ / dV value corresponding to the voltage of 0.45V is I 0.45value.
[0128] in, Figure 6 This is a voltage-dQ / dV curve of the silicon-carbon material prepared in Example 4.
[0129] 6. TEM-EDS test: The test instrument is JEM-2100UHR transmission electron microscope.
[0130] The above test results are listed in Table 2:
[0131] Table 2
[0132]
[0133]
[0134] According to the above table, the difference in D50 particle size between the silicon-carbon materials of Examples 1-8 at 0T pressure and 20T pressure is less than 5.1 μm, and the difference in D50 particle size between the silicon-carbon materials of Examples 1-8 at 5T pressure and 20T pressure is less than 2.3 μm, indicating that the silicon-carbon materials of Examples 1-8 have excellent strength.
[0135] The difference in D50 particle size between the silicon-carbon material prepared in Comparative Example 1 under a pressure of 0T and a pressure of 20T is 6 μm, and the strength of the silicon-carbon material is significantly deteriorated.
[0136] Figure 5 TEM-EDS images of a silicon layer and a carbon layer in Example 1.
[0137] Effect Example 2
[0138] Button battery assembly:
[0139] The positive electrode adopts the negative electrode sheet prepared by Examples 1-9 and Comparative Examples 1-7; the negative electrode adopts a lithium sheet; the electrolyte adopts the following formula composition by mass: EC 10%, PC 15%, DEC 20%, PP 30%, LiPF6 15%, FEC 6%, PS2.5%, LiODFB 1.5%; the amount of electrolyte added in the button battery is 0.5g.
[0140] The following tests were performed on the half-cells assembled from the above Examples 1-9 and Comparative Examples 1-7:
[0141] 1. Cycle failure test:
[0142] (1) 0.5C 1.5V cycle failure number (measured at 25°C): The above button cell was discharged at a constant voltage discharge rate of 0.1V / h to 0.000V, then charged at 0.1V / h to 1.5V, and the charging capacity was recorded. A button cell was reassembled and a constant current charge and discharge test was performed at 0.5C with the charging capacity recorded. The battery was repeatedly charged and discharged from 0V to 1.5V, and the discharge capacity was recorded. The battery was terminated when the discharge capacity reached 60% of the gram capacity at 0.1C and 1.5V, and the number of cycles was recorded.
[0143] (2) 1C 1.5V cycle failure number (measured at 25°C): The above button cell was discharged at a constant voltage discharge rate of 0.1V / h to 0.000V, then charged at 0.1V / h to 1.5V, and the charging capacity was recorded. A button cell was reassembled and a constant current charge and discharge test was performed at 1C with the charging capacity recorded. The battery was repeatedly charged and discharged from 0V to 1.5V, and the discharge capacity was recorded. The test was terminated when the discharge capacity reached 60% of the gram capacity at 0.1C and 1.5V, and the number of cycles was recorded.
[0144] 0.1C, 1.5V gram capacity test: The above button battery was discharged at a constant voltage of 0.1V / h to 0.000V, then charged at 0.1V / h to 1.5V, and the charging capacity of 0.5C was recorded. A button battery was reassembled and a constant current charge and discharge test was performed to record the charging capacity of 0.1C. After discharging to 0V, it was charged to 1.5V. After obtaining the capacity, the gram capacity of 0.1C, 1.5V was obtained using the capacity / mass of active material in the electrode method.
[0145] 2. Different rate retention test: 1C rate cycle / 0.5C cycle;
[0146] The calculation method of the retention rate (%) at different rates at 25℃ is: 1C 25℃ cycle failure number / 0.5C 25℃ cycle failure number.
[0147] 3. First effect: Use constant voltage discharge method, discharge to 0.000V at 0.1V / h, then charge to 1.5V at 0.1 / h, record the charge and discharge capacity, and get the first effect by lithium removal capacity / lithium insertion capacity.
[0148] The above test results are listed in Table 3:
[0149] Table 3
[0150]
[0151] According to the above table, the 0.1C and 1.5V gram capacities of the silicon-carbon materials prepared in Examples 1-9 of the present invention can reach more than 2076 mAh / g, the 1.5V first efficiency can reach more than 90.4%, the 0.5C 25°C cycle failure number can reach more than 184 cycles, the 1C 25°C cycle failure number can reach more than 301 cycles, and the 25°C rate retention rate can reach more than 49%. This shows that the above silicon-carbon materials can have excellent cycle performance and rate performance when used in batteries.
[0152] Comparative Example 1 adopts a conventional preparation method, uses porous carbon with a high specific surface area as the central core, and uses acetylene as a carbon source for carbon deposition, and its gram capacity is reduced to 1989 mAh / g.
[0153] Comparative Example 2 uses a central nucleation point with an excessively high ID / IG value, and its gram capacity is reduced to 1857 mAh / g.
[0154] Comparative Example 4 uses too low a specific surface area of the central nucleation point, resulting in a decrease in its 0.1C, 1.5V gram capacity, 1.5V first efficiency, 1C 25°C cycle failure number and 25°C rate retention rate. Comparative Example 5 uses too high a specific surface area of the central nucleation point, which is not conducive to its 1C 25°C cycle failure number.
[0155] Comparative Example 6 uses a carbon source with too low molecular weight, resulting in a decrease in its 0.1C, 1.5V gram capacity, 1C 25°C cycle failure number and 25°C rate retention rate. Comparative Example 7 uses a carbon source with too low molecular weight, which is not conducive to its 1C 25°C cycle failure number.
Claims
1. A silicon-carbon material, characterized in that: It includes a central core and a silicon-carbon alternating layer covering the surface of the central core, wherein the silicon-carbon alternating layer includes at least one silicon layer and at least one carbon layer, the silicon layer and the carbon layer are arranged alternately, the layer adjacent to the central core is a silicon layer, and the outermost layer of the concentric circle structure is a carbon layer; The central core is a carbon sphere, the ID / IG value of the central core is 0.2-0.7, and the specific surface area of the central core is 60-300m 2 / g; Wherein, the carbon layer is a soft carbon-like structure.
2. The silicon-carbon material according to claim 1, characterized in that The silicon-carbon material is a concentric circle structure; And / or, in the silicon-carbon alternating layer, the thickness ratio of every two adjacent carbon layers to silicon layers is (1-10):1; And / or, the number of layers of the silicon layer is 3-20 layers, for example, 10 layers; And / or, the silicon-carbon material I 0.45 The value is less than 55mah / v; And / or, the true density of the central core is 1.5-2.5 g / cm 3 , for example 2.2 g / cm 3 or 1.98 g / cm 3 ; And / or, the silicon content of the silicon-carbon material is 50%-85%, for example, 51.3%, 57.9%, 63.1%, 68.6%, 73.6%, 78.9%, 81.1% or 84.5%, wherein the silicon content means the mass percentage of silicon to the mass percentage of the silicon-carbon material; And / or, the carbon content of the silicon-carbon material is 15%-50%, for example, 48.7%, 42.1%, 36.9%, 31.4%, 26.4%, 21.1%, 18.9% or 15.5%, wherein the carbon content means the mass percentage of carbon to the mass percentage of the silicon-carbon material.
3. The silicon-carbon material according to claim 1, characterized in that: The ID / IG value of the central core is 0.3-0.6, for example 0.4; And / or, the specific surface area of the central core is 10-200m 2 / g, for example, 121m 2 / g or 50m 2 / g; And / or, the D50 particle size of the central core is 0.5-3 μm, for example, 1 μm; And / or, the (D90-D10) / D50 value of the central core is 0.5-5, for example, 1.
4. A method for preparing a silicon-carbon material, characterized in that: It includes the following steps: Performing silicon-carbon alternating deposition on the central nucleation point; the silicon-carbon alternating deposition includes at least one silicon deposition and at least one carbon deposition, the silicon deposition and the carbon deposition are performed alternately, and the first deposition is silicon deposition, and the last deposition is carbon deposition; The central nucleation point is a carbon sphere, the ID / IG value of the central nucleation point is 0.2-0.7, and the specific surface area of the central nucleation point is 60-300m 2 / g; Wherein, the carbon deposition adopts a carbon source with a molecular weight of 100-1000.
5. The method for preparing the silicon-carbon material according to claim 4, characterized in that: The ID / IG value of the central nucleation point is 0.3-0.6, for example 0.4; And / or, the specific surface area of the central nucleation point is 60-200m 2 / g, for example, 121m 2 / g; And / or, the true density of the central nucleation point is 1.5-2.5 g / cm 3 , for example 2.2 g / cm 3 or 1.98 g / cm 3 ; And / or, the D50 particle size of the central nucleation point is 0.5-3 μm, for example, 1 μm; And / or, the (D90-D10) / D50 value of the central nucleation point is 0.5-5, for example, 1.
6. The method for preparing the silicon-carbon material according to claim 4, characterized in that: The number of times of silicon deposition is 3-20 times, for example, 10 times; And / or, the carbon source is one or more of condensed ring aromatic hydrocarbons, mixtures containing condensed ring aromatic hydrocarbons, alkanes, mixtures containing alkanes and asphalt; Wherein, the number of C atoms of the alkane is preferably 10-30; Preferably, the carbon source is one or more of anthracene, anthracene oil, coal tar pitch and paraffin; Wherein, the carbon source is preferably anthracene oil, and the molecular weight of the anthracene oil is preferably 1000; And / or, the molecular weight of the carbon source is 150-1000, for example, 178, 200, 500 or 1000.
7. The method for preparing the silicon-carbon material according to claim 4, characterized in that: The silicon deposition is carried out by chemical vapor deposition; Wherein, the temperature of silicon deposition is preferably 450-700° C., more preferably 500-700° C., for example 550° C.; Before silicon deposition, the temperature of the environment in which the silicon source used for silicon deposition is located is preferably maintained at 300-400° C., for example, 350° C.; The flow rate of the silicon source gas is 0.5-50 L·kg -1 ·min -1 , for example 5L·kg -1 ·min -1 ; Wherein, the silicon deposition time is preferably 1-40 min, more preferably 1-30 min; And / or, the carbon deposition is performed by chemical vapor deposition; wherein the temperature of the carbon deposition is preferably 600-1000° C., for example 800° C.; Wherein, the carbon deposition time is preferably 1-100 min, for example, 5 min; Before the carbon deposition is performed, the temperature of the environment in which the carbon source used for the carbon deposition is preferably maintained at 300-400° C., for example, 350° C.; The flow rate of the carbon source gas is 0.5-50 L kg -1 ·min -1 , for example 5L·kg -1 ·min -1 ; Wherein, the carbon deposition preferably also uses a protective gas, and the protective gas is, for example, one or more of nitrogen, helium and argon; The protective gas and the carbon source gas are introduced in the form of a mixed gas; wherein the flow rate of the mixed gas is 1-100 L·kg -1 ·min -1 , for example, 10L kg -1 ·min -1 ; Wherein, the flow rate of the protective gas is 0.5-50L·kg -1 ·min -1 , for example 5L·kg -1 ·min -1 ; Before the carbon deposition is performed, the temperature of the environment in which the carbon source and the protective gas used for the carbon deposition are preferably maintained at 300-400°C, for example, 350°C; Before forming the carbon source gas, the temperature of the environment where the carbon source is located is preferably maintained at 300-400°C, such as 350°C; before forming the carbon source gas, the pressure of the environment where the carbon source is located is preferably maintained at 20Kpa-80Kpa.
8. The method for preparing a silicon-carbon material according to any one of claims 4 to 7, characterized in that: The preparation method of the silicon-carbon material is carried out in a vapor deposition device, which includes a gas generator, a mixer and a reaction furnace; the gas generator is provided with a first gas outlet, the mixer includes a first gas inlet, a second gas inlet and a deposition gas outlet arranged at different positions, the reaction furnace is provided with a deposition gas inlet, the first gas outlet of the gas generator is communicated with the first gas inlet of the mixer, and the deposition gas outlet of the mixer is communicated with the deposition gas inlet of the reaction furnace; When carbon deposition is performed, the gas generator is used to generate a carbon source gas, the carbon source gas is sequentially introduced into the mixer through the first gas outlet and the first gas inlet of the mixer, and then sequentially enters the reaction furnace through the deposition gas outlet of the mixer and the deposition gas inlet of the reaction furnace; carbon deposition is performed in the reaction furnace; When silicon deposition is performed, the silicon source gas used for the silicon deposition is introduced into the mixer through the second gas inlet, and then enters the reaction furnace through the deposition gas outlet of the mixer and the deposition gas inlet of the reaction furnace in sequence, and silicon deposition is performed in the reaction furnace.
9. A silicon-carbon material obtained by the method for preparing a silicon-carbon material as claimed in any one of claims 4 to 8.
10. A lithium ion battery, characterized in that: It comprises the silicon-carbon material as described in any one of claims 1-3 and 9.